Broadening the evidence for the theory of planned behavior: predicting heavy episodic drinking in Argentinean female and male youth - Peltzer, Raquel Inés (2017)
Introduction. Although the Theory of Planned Behavior has successfully been applied to explain heavy episodic drinking, recent reviews have identified gaps in the literature like the role of gender and scarce research from non English speaking countries. Objective. We aim to broaden the evidence for the Theory of Planned Behavior by evaluating the capacity of the model to predict heavy episodic drinking in Argentinean female and male youth. Methods. Multiple linear and logistic regressions were performed. Results. Attitude was the main predictor of heavy episodic drinking intention; there were gender differences, among women perceived behavioral control and subjective norm were also predictors of heavy episodic drinking intentions. The intention was the main predictor of heavy episodic drinking for both genders, while perceived behavioral control was also a predictor among women. Conclusions. Theory of Planned Behavior allows us to better understand the motivational variables related to heavy episodic drinking intention and performance, and thus, to design appropriate prevention interventions.